Discover France - Berry, Oliver; Lonely Planet Publications (Firm) (Footscray, Vic. : Lonely Planet, 2011)
All you need to experience the best of France. We've selected the most iconic sights and incredible places so you can enjoy the real France with the minimum fuss. Discover guides are travel made easy, with Lonely Planet's trademark insider tips, helpful maps and destination expertise.
"Experience the best of France"--Cover.
Fold-out map inside back cover.
Includes bibliographical references and index.
Keywords: France -- Guidebooks; France -- Description and travel